Minimaxity, Statistical Thinking and Differential Privacy - Wasserman, Larry (Journal of Privacy and Confidentiality, 2012)
We discuss the role of minimax statistical theory for privacy theory. Minimax theory gives a way to measure information loss for sanitized databases. We also discuss some differences between privacy theory from the statistical perspective versus the computer science perspective.